The Conditions for Higher Education Institutions to Meet the Social Challenges Ahead - Yves Flückiger (Ali Khorsandi Taskoh, 2021)
Universities are among the oldest institutions in the world. They have a history, forged through wars, religious conflicts and all the revolutions they have always survived. They also make history and build the future. Today, they are more essential than ever. Secular, they have a trajectory oriented towards the future; it is to them that we turn to respond to the issues and challenges that our societies must face. Through dialogue, the creation of knowledge, the transmission of culture, they are the place of freedom of thought, of the search for truth, even if this search sometimes contradicts established convictions and too easily accepted ideas. Universities are the antithesis of all fanaticism. In this sense, they remain one of the most precious constructions of humanity. In order to achieve this status, to continually reinvent themselves without losing their soul, without losing sight of their primary missions, linked to teaching and research, universities have had to be innovative, again and again. They have been able to adapt because, precisely, through teaching and research, they are constantly questioning the world, participating in and anticipating its transformations. In order for them to continue to play this role, some conditions must be met. Let me present them one by one before I can share my dream, that of an academic world capable of offering all its potential to ensure sustainable development to all our societies for a fairer world.